Identification of the light-independent phosphoserine pathway as an additional source of serine in the cyanobacterium Synechocystis sp. PCC 6803 - Klemke, Friederike; Baier, Antje; Knoop, Henning; Kern, Ramona; Jablonsky, Jiri; Beyer, Gabriele; Volkmer, Thomas; Steuer, Ralf; Lockau, Wolfgang; Hagemann, Martin (Microbiology (Reading, England), 2015)
L-serine is one of the proteinogenic amino acids and participates in several essential processes in all organisms. In plants, the light-dependent photorespiratory and the light-independent phosphoserine pathways contribute to serine biosynthesis. In cyanobacteria, the light-dependent photorespiratory pathway for serine synthesis is well characterized, but the phosphoserine pathway has not been identified. Here, we investigated three candidate genes for enzymes of the phosphoserine pathway in Synechocystis sp. PCC 6803. Only the gene for the D-3-phosphoglycerate dehydrogenase is correctly annotated in the genome database, whereas the 3-phosphoserine transaminase and 3-phosphoserine phosphatase (PSP) proteins are incorrectly annotated and were identified here. All enzymes were obtained as recombinant proteins and showed the activities necessary to catalyse the three-step phosphoserine pathway. The genes coding for the phosphoserine pathway were found in most cyanobacterial genomes listed in CyanoBase. The pathway seems to be essential for cyanobacteria, because it was impossible to mutate the gene coding for PSP in Synechocystis sp. PCC 6803 or in Synechococcus elongatus PCC 7942. A model approach indicates a 30-60% contribution of the phosphoserine pathway to the overall serine pool. Hence, this study verified that cyanobacteria, similar to plants, use the phosphoserine pathway in addition to photorespiration for serine biosynthesis.
Keywords: substrátová specifita; sekvenční seřazení; Phosphoglycerate Dehydrogenase; Gene Expression Regulation, Enzymologic; Molecular Sequence Data; fosfoglycerátdehydrogenasa; sekvence aminokyselin; Light; Enzyme Activation; Phosphoserine; světlo; fosfoserin; regulace genové exprese enzymů; metabolické sítě a dráhy; Substrate Specificity; serin; Metabolic Networks and Pathways; Sequence Alignment; aktivace enzymů; Serine; Synechocystis; Amino Acid Sequence; molekulární sekvence - údaje